2004
DOI: 10.1128/jb.186.3.803-810.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Transaminase B (IlvE) Activity Caused by the Lack ofyjgFIs Dependent on the Status of Threonine Deaminase (IlvA) inSalmonella entericaSerovar Typhimurium

Abstract: The YjgF/YER057c/UK114 family is a highly conserved class of proteins that is represented in the three domains of life. Thus far, a biochemical function demonstrated for these proteins in vivo or in vitro has yet to be defined. In several organisms, strains lacking a YjgF homolog have a defect in branched-chain amino acid biosynthesis. This study probes the connection between yjgF and isoleucine biosynthesis in Salmonella enterica. In strains lacking yjgF the specific activity of transaminase B, catalyzing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(118 citation statements)
references
References 64 publications
(47 reference statements)
10
108
0
Order By: Relevance
“…This activity has two anticipated consequences in vivo: 1) increasing the hydration rates in low water environment to improve product generation and 2) removing reactive metabolites. We suggest that the diverse phenotypes described for ridA (yjgF) mutants in S. enterica (10,11,13,33) result from the accumulation of enamine/imine intermediates and that the nucleophilic nature of these metabolites allows them to react with and modify cellular targets, altering their function. The plausibility of this scenario is supported by literature reports that the aminoacrylate enamine derived from serine can inactivate a number of enzymes in vitro (43,44).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This activity has two anticipated consequences in vivo: 1) increasing the hydration rates in low water environment to improve product generation and 2) removing reactive metabolites. We suggest that the diverse phenotypes described for ridA (yjgF) mutants in S. enterica (10,11,13,33) result from the accumulation of enamine/imine intermediates and that the nucleophilic nature of these metabolites allows them to react with and modify cellular targets, altering their function. The plausibility of this scenario is supported by literature reports that the aminoacrylate enamine derived from serine can inactivate a number of enzymes in vitro (43,44).…”
Section: Discussionmentioning
confidence: 98%
“…Past work, primarily in S. enterica, suggested that the diverse phenotypes of yjgF mutants reflected a global metabolic role for this protein family (11)(12)(13)33). The results reported herein define an enamine/ imine deaminase activity associated with the YjgF protein and homologs from all domains of life, including humans.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results suggest the X-NH 3 metabolite is unstable, perhaps favoring an explanation involving a reaction intermediate rather than a byproduct. 5 The ability of YjgF protein to inhibit the TrpD-dependent PRA formation in vitro was predicted by both in vivo phenotypes and the working model for this class of proteins (8,10,11). The inhibition of PRA formation by YjgF displayed several features that provided insights into the function of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, why deleting yjgF restores PRA formation is unknown. Based on previous work by our laboratory and by others, it has been proposed that YjgF interacts with and possibly sequesters small, potentially toxic molecules, thus altering the metabolic environment of the cell (10,11).…”
mentioning
confidence: 99%
“…Two of them are directly or indirectly linked to amino acid synthesis: Asd is an aspartate-semialdehyde dehydrogenase involved in lysine biosynthesis and was identified as a unique spot in mutant M18E10. The abundance of YjgF in M18E10 was about 3.4 times greater than that in the parental strain; this protein is involved in isoleucine biosynthesis (Schmitz & Downs, 2004).…”
Section: Proteins Regulated By Yjjqmentioning
confidence: 85%